2022
DOI: 10.1111/jch.14485
|View full text |Cite
|
Sign up to set email alerts
|

Potential triggering factors associated with aneurysmal subarachnoid hemorrhage: A large single‐center retrospective study

Abstract: Controlling blood pressure levels is critical to preventing intracranial aneurysm rupture, and a summary review of induced rupture events allows better health education for patients. We retrospectively reviewed all medical records of consecutive patients with aneurysmal subarachnoid hemorrhage (aSAH) admitted to Beijing Tiantan Hospital from 2015 to 2020. We collected patients' demographic information, aneurysm morphology, blood pressure level on admission, time to onset, and events at the time of aneurysm rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The late recovery of patients is very important, which is related to their overall recovery [22,23]. Therefore, in the process of postoperative rehabilitation, health education needs to be strengthened before discharge, so as to make patients understand the precautions to be taken after discharge, ensure regular work and [24], which are similar to our findings. Our results together suggest that effective nursing interventions can accelerate patients' recovery, guide the postoperative rehabilitation, and contribute to relieving clinical symptoms, shortening hospital stay, as well as improving prognosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The late recovery of patients is very important, which is related to their overall recovery [22,23]. Therefore, in the process of postoperative rehabilitation, health education needs to be strengthened before discharge, so as to make patients understand the precautions to be taken after discharge, ensure regular work and [24], which are similar to our findings. Our results together suggest that effective nursing interventions can accelerate patients' recovery, guide the postoperative rehabilitation, and contribute to relieving clinical symptoms, shortening hospital stay, as well as improving prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…Study has shown that postoperative patients are prone to obstructed limb blood circulation and gastrointestinal peristalsis due to prolonged bed rest, which can lead to a variety of rest time, adhere to the healthy behaviors, and comply with the medical advice to review on time to get a good rehabilitation results [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted in Beijing found that the incidence of ruptures of intracranial aneurysms was higher in seasons with higher average temperatures. The study also reported that it was higher in seasons with more significant temperature variations [9].…”
Section: Temperaturementioning
confidence: 79%
“…The differences in the numbers of events are statistically significant, since the number of cases for 4745 days (13 years) allows to identify differences, which can be small but still statistical significant. A recent study indicates hypertension, as well as arguing or quarrelling and seasonality (autumn) as a risk factors of aneurysm rupture [ 2 ]. Carnival is such a period of arguing and quarreling, where we see a rise of SAH.…”
mentioning
confidence: 99%